The Legal Consequences of Electronic Land Certificate Checking Services for PPAT - Salsabil, Haura Hanun (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to analyze the processes and constraints in the service of checking land certificates electronically for PPATs in the Semarang Regency Region. The research method used is a normative legal research method with a conceptual approach. The method of data analysis used in this research is through a sociological juridical approach with descriptive research specifications. Data collection techniques used field studies at research locations and literature studies related to research. Based on the research it was concluded that the research results showed that: First, the process of implementing an electronic certificate service system at the Semarang District Land Office refers to a simple principle, very simple because checking certificates electronically is very easy because the PPAT only enters data on land rights certificates electronically on the website intan.atrbpn.go.id. Second, in the implementation of the Electronic Certificate Checking Service there are several obstacles, obstacles, and problems that can cause legal consequences for both the PPAT and the Land Office/BPN.Keywords: Certificate; Electronic; Land.